Aloe ×selmarii (Asphodelaceae subfam. Alooideae), a new nothospecies from South Africa, with A. davyana var. davyana and A. parvibracteata as parents - Smith, Gideon F.; Klopper, Ronell R. (Phytotaxa, 2021)
Aloe ×selmarii (Asphodelaceae subfam. Alooideae), a hybrid between A. davyana var. davyana and A. parvibracteata, is described. Although the natural distribution ranges of the parent species do not overlap, this nothospecies is often encountered as a result of the cultivation of A. parvibracteata outside its natural range, in areas where A. davyana var. davyana occurs naturally.